INTERIOR ISLAM : ANTARA OTORITAS DAN KESALEHAN MUSLIM DI BOJONEGORO - Arifin (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2023)
This article will examine the Muslim community in the hinterland of Bojonegoro, to be precise in Glingsem Hamlet, Soko Village, Temayang District. By tracing the praxis of the formation of the Jamaah, and a charismatic figure, who is recognized as a descendant of the Prophet, Habib Fauzi al-Jufri. Apart from that, this article also explores how the piety of a Muslim is formed by following the congregation which is routinely carried out during Selapanan (a term in Javanese in 36 days). Departing from the assumption that religious authority has shifted due to globalization and has formed a new authority in understanding religion which is marked by the consumption of social media. With an ethnographic review that went down and directly followed the events carried out in the routine of the Jamaah for 6 months, which started from early February to 6 July 2023, the researcher found that the authority formed through the Jamaah was able to shape Muslim piety awareness. Using Anthropological analysis with a historical praxis approach, this article in analyzing Religious Authority follows the work of Ismail Fajri al-Attas entitled